STUDYING AND CALCULATION of THE SPECTRALPROPERTIES FOR SIF MOLECULE VIBRATIONS BY SEMIEMPIRICAL PROGRAMS - Haider, Haider; Mahdi, Wissam (Iraqi Journal of Science, 2024)
this research, the more important spectral properties of vibration SiF moleculehave been studied and calculated by using the semi-empirical theoretical programsin method (MNDO/PM3). The wave lengths of that vibrations have been calculatedand symmetric both of them. Also, the geometric space shape of ion has beencalculated by using initial and final matrices that include bonds length, the anglebetween bonds, dihedral angles and the charge of each atom in ion.Total energy, Binding energy, Electronic energy, Core-core repulsion, Ionizationpotential and Molecular weight have been calculated. Also, the curve of potential ofion was drawn where it depend on the changing in bond length of (Si-F) verses theopposite energy value. In addition, the energy value of molecular orbital wascomputed with calculation of the energy of the highest occupied molecular orbital(HOMO) and the lowest unoccupied molecular orbital (LUMO).